2014
DOI: 10.4049/jimmunol.1301376
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Embryonic Hematopoiesis by a Cytokine-Inducible SH2 Domain Homolog in Zebrafish

Abstract: Cytokine-inducible SH2 domain–containing protein (CISH), a member of the suppressor of cytokine signaling family of negative feedback regulators, is induced by cytokines that activate STAT5 and can inhibit STAT5 signaling in vitro. However, demonstration of a definitive in vivo role for CISH during development has remained elusive. This study employed expression analysis and morpholino-mediated knockdown in zebrafish in concert with bioinformatics and biochemical approaches to investigate CISH function. Two ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“….TTCN 3 GAA) in its promoter, and knockdown of cish.a, but not cish.b, resulted in enhanced embryonic erythropoiesis, myelopoiesis, and lymphopoiesis. This study showed conserved CIS functions for the control of hematopoiesis through STAT5 (Lewis et al 2014).…”
Section: Cis: Inhibitor Of Cytokine and T-cell Receptor (Tcr) Signalingmentioning
confidence: 64%
“….TTCN 3 GAA) in its promoter, and knockdown of cish.a, but not cish.b, resulted in enhanced embryonic erythropoiesis, myelopoiesis, and lymphopoiesis. This study showed conserved CIS functions for the control of hematopoiesis through STAT5 (Lewis et al 2014).…”
Section: Cis: Inhibitor Of Cytokine and T-cell Receptor (Tcr) Signalingmentioning
confidence: 64%
“…This was evidenced from CISH transgenic mice, which showed increased Th2 polarization proposed to be due to suppressive effects of CISH on IL-2 signaling, including STAT5 activation ( 250 ), with CISH able to bind to the IL-2 receptor β chain component, which blocks activation of the associated JAK3 ( 48 ). A similar mechanism is likely to explain the heightened embryonic lymphopoiesis observed following knockdown of the zebrafish CISH paralogue Cish.a, which also correlated with enhanced STAT5 activation ( 251 ). CISH −/− mice suffered from airway inflammation and progressively developed a pulmonary disease characterized by enhanced eosinophils within the airways and epithelial cell hyperplasia ( 51 ).…”
Section: Socs Proteins As Regulators Of Immunity and Its Perturbation In Diseasementioning
confidence: 94%
“…In vitro transcription and translation of socs4a mRNA in the presence of MOs was performed as described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%